Development and optimisation of a process for cellulose nanoparticle production from waste paper sludge with enzymatic hydrolysis as an integral part - Bester, Lia Mari (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.